Levantamiento Topográfico Georreferenciado con Fotogrametría - Lupera Parra, Jorge Andrés (2020)
The use of technology during the last decade has become vertiginous, that is to say its use is of the first necessity to be able to develop ideas and arrive at precise conclusions. In the agricultural sector has not been the exception, the use of unmanned aerial objects (drones) in this area so important for our country, has become common because of the speed of being able to obtain information, currently it is not necessary to go through the crops personally to be able to observe the different problems that may arise, studies can be carried out using state-of-the-art technology such as drones with a high-definition camera, the efficiency of these objects helps in seeding, fumigation, etc., both economically and environmentally. This work aims to publicize the latest renovations and acquisitions obtained by the Faculty of Agronomic Sciences of the Technical University of Babahoyo showing its development and growth over time. In order to develop this project, the georeferenced topographic survey was carried out with photogrammetry of the place under study showing the advances that have been made in the 220 hectares of this faculty, such as classroom blocks, banana trees, etc. Subsequently, the measures referenced were grouped through photographic shots using the drone to form a mosaic photo that is an image made up of rectangular shots. The conclusions of this project determine the progress that the Faculty of Agronomic Sciences has had in its last years thanks to the management of its different managers ensuring the development of each of its students so that their experience within this field of studies is becoming more and more pleasant.